Colloid-facilitated mobilization of cadmium: Comparison of spring freeze-thaw event and autumn freeze-thaw event - Hu, Nai-Wen; Yu, Hong-Wen; Wang, Qi-Rong; Zhu, Guo-Peng; Yang, Xiu-Tao; Wang, Tian-Ye; Wang, Yang; Wang, Quan-Ying (The Science of the total environment, 2022)
Freeze-thaw action has the potential to facilitate the mobilization of colloid-associated contaminants in soil. However, the differences in colloid-associated contaminants following autumn freeze-thaw (AFT) events and spring freeze-thaw (SFT) events remain unclear. In this study, the potential influence mechanisms of AFT and SFT on both the generation and migration of colloids and colloid-associated cadmium (Cd) in soil were explored. Higher aggregate stabilities were found in soils after AFT compared with after SFT. After SFT, lower Cd concentrations were found in soil aggregates of 0.25–0.50 mm and <0.106 mm and higher concentrations were found in 0.106–0.25 mm aggregates. Moreover, SFT generated higher amounts of colloidal Cd than AFT, while AFT increased the total Cd concentration in leachates. Additionally, compared with SFT, AFT led to higher Cd concentrations in dissolved and colloid-associated forms in leachates. These findings demonstrate that higher amounts of colloid and fewer loadings of Cd in colloids in Cd contaminated soil can be found after SFT events. Thus, to better understand the environmental risk of contaminants in areas subject to seasonal freeze-thaw cycles, the differences between freeze-thaw processes in spring and autumn should be considered. [Display omitted] •Higher soil aggregate stability is found under freeze-thaw cycles in autumn.•Freeze-thaw cycles in spring enhance the generation of colloids in soil.•Autumn freeze-thaw leads to the increase of total Cd concentrations in leachates.•Concentration of dissolved Cd in leachates is higher for autumn freeze-thaw cycles.•Lower colloidal bound Cd concentration is found under freeze-thaw cycles in spring.